Design Of Expert System To Diagnose Sexually Infected Diseases In Human Using The Backward Chaining Method (Perancangan Sistem Pakar Untuk Mendiagnosa Penyakit Menular Seksual Pada Manusia Dengan Penerapan Metode Backward Chaining) - Harkamsyah Andrianof (Jurnal KomtekInfo, 2019)
Expert systems (expert systems) in general is trying to adopt a system of human knowledge into a computer, so the computer can resolve the problem as was done by the experts. Or in other words, the expert system is a system designed and implemented with the help of a specific programming language to be able to resolve the problem as done by experts. In this case I tried to implement an expert system to diagnose sexually transmitted disease from the symptoms and the causes of Sexually Transmitted Disease. The purpose of this paper is to build a knowledge-based system on Sexually Transmitted Disease using backward chaining method that will be displayed in the form of a website using PHP programming and MySQL database.